POTENSI DAN STRATEGI PENGEMBANGAN DESA SUMBERSALAK SEBAGAI DESA WISATA - Bagus Indra Tjayadhi (MEDIAKOM : Jurnal Ilmu Komunikasi, 2020)
The purpose of this research is analyzing tourism potential and development strategic as a tourism village in Sumbersalak Village, Jember Regency. This research based on quantitative and qualitative method. Quantitive data based on from observations and interview with questionaires besides, the supporting data was from library resources.Based on SWOT analysis result found the internal factors and external factor. The internal factors consist of (1) strength: beautiful natural resources and products from the village people, (2) weaknesess: Sumbersalak village need more development about human resources and infastucture, external factors (1) opportunity: the uniqueness of natural resources and people culture, (2) threat: competition of with other village in the development of rural tourism. Based on SWOT analysis obtained the development strategy for Sumbersalak village is using WO strategy. This strategy need to minimize most of the threat that they have and getting the big opportunity become good management of rural tourism